The Society Famous Sport: The Analyzing Study of Sport for Banda Aceh Community in New Normal Era - Pranata, Didi Yudha; Rahmat, Zikrur; Munzir, Munzir; Sarwita, Tuti; Irfandi, Irfandi; Irwandi, Irwandi; Mukhlisuddin, Mukhlisuddin (Jurnal Ilmiah Teunuleh, 2023)
The purpose of this study is to determine the favorite sport of the people of Banda Aceh City in the new normal era. descriptive research method with survey techniques. The sampling technique used random sampling techniques, the object was 350 people. Data collection techniques using google form. The data analysis technique used descriptive statistics. The results of the study were sports carried out by the people of Banda Aceh in the new normal era, including jogging by 58.3%, cycling by 27.8%, martial arts 4.3%, badminton sports 4.3% and agility sports 1.9%. Based on the results of the study it can be concluded that the favorite sport of the people of Banda Aceh in the new normal era is jogging.